Exploring the Innovativeness, Proactiveness, Risk Taking, CSR Support, Organizational Engagement, Job Engagement, and Creativity on PR Tirta Bangunan Baru - Hutabarat, Zoel; Kuswanto, Khennedy (Proceeding of International Conference on Entrepreneurship (IConEnt), 2023)
Companies that exist all around the world need to have the skills. Those skills are needed to become a flourishing company, because it’s not just about strategies or goals. It's also bound by the worker in that company. That bond is the worker or the employees of that company that contribute to the company which makes a difference against other competitors. The purpose of this research is to analyze the factors that employees need to be able to contribute by Innovativeness, Proactiveness, Risk Taking, CSR Support, Organizational Engagement, Job Engagement, and Creativity to the company. The data gathered was through the use of a survey approach using google forms in a series of questionnaires. The subject of this research is the employees of PT.Tirta Bangunan Baru. The method used is quantitative research and a purposive sampling is used for this research, The Partial Least Square Structural Equation Modelling which is SMART-PLS SEM is used for the technique to scrutinise the data (v 4.0.8.4). Validity and reliability tests were performed in this study with a pretest of 40 respondents. Furthermore, a total of 210 respondents were chosen for the sample size of this study. Additionally, the data concluded having 9 supported hypotheses and 2 not supported hypotheses from all 11 hypotheses that are included in this research. The data that has been gathered produced results to show all the variables examined had a positive effect on PT.Tirta Bangunan Baru employees.